2016
DOI: 10.1111/tan.12900
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐associated antigens: Tn antigen, sTn antigen, and T antigen

Abstract: Glycosylation is one of the major posttranslational modifications of proteins. N-glycosylation (Asn-linked) and O-glycosylation (Ser/Thr-linked) are the two main forms. Abnormal O-glycosylation is frequently observed on the surface of tumor cells, and is associated with an adverse outcome and poor prognosis in patients with cancer. O-glycans (Tn, sTn, and T antigen) can be synthesized in the Golgi apparatus with the aid of several glycosyltransferases (such as T-synthase and ST6GalNAc-I) in a suitable environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
148
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(160 citation statements)
references
References 97 publications
2
148
0
Order By: Relevance
“…It has been well documented that Tn antigen is one of the most expressed tumour antigen found in many human cancers, such as colon, breast, cervix, stomach and skin . Many studies have established an association of Tn antigen expression with cancer progression and metastasis and poor outcome . However, it is still unclear whether Tn antigen plays a causative role in cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well documented that Tn antigen is one of the most expressed tumour antigen found in many human cancers, such as colon, breast, cervix, stomach and skin . Many studies have established an association of Tn antigen expression with cancer progression and metastasis and poor outcome . However, it is still unclear whether Tn antigen plays a causative role in cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of O‐glycosylation, the Tn antigen is normally modified to form elongated and complex O‐glycans by a specific galactosyltransferase (T‐synthase) in the Golgi apparatus of cells and is thereby not detectable in normal tissues . T‐synthase and its unique chaperone Cosmc are indispensable for normal O‐glycosylation . As many studies revealed that dysfunction in Cosmc (mutations, deletion, and hypermethylation) is a prevailing mechanism for Tn antigen expression in various human cancers, we focused our attention on the functional role of Tn antigen by induction of Cosmc deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, we examined the expression of Tn antigen, T‐synthase, and ppGalNac‐Ts, which are essential components during the process of O‐glycosylation, in CRC cells. Alterations in Tn antigen, T‐synthase and/or ppGalNac‐Ts are indicative of aberrant O‐glycosylation . We first detected Tn antigen expression in both Cosmc‐overexpressing cells via flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…We thereby sought to explore the mechanisms for elevated sion and T antigen production, which was the mechanism for the altered cellular phenotypes. 15 Here we checked the changes of Tn, T-synthase, and several essential ppGalNAc-Ts, which are key components of normal O-glycosylation, 21,24,26…”
Section: Discussionmentioning
confidence: 99%